2010
DOI: 10.1016/j.jfa.2009.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Infinitesimal non-crossing cumulants and free probability of type B

Abstract: Free probabilistic considerations of type B first appeared in the paper of Biane, Goodman and Nica [P. Biane, F. Goodman, A. Nica, Non-crossing cumulants of type B, Trans. Amer. Math. Soc. 355 (2003Soc. 355 ( ) 2263Soc. 355 ( -2303. Recently, connections between type B and infinitesimal free probability were put into evidence by Belinschi and Shlyakhtenko [S.T. Belinschi, D. Shlyakhtenko, Free probability of type B: Analytic aspects and applications, preprint, 2009, available online at www.arxiv.org under ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 10 publications
0
55
0
Order By: Relevance
“…, A k . One has, as found in [11], a natural way of defining a family (κ ′ n : A n → C) ∞ n=1 of infinitesimal free cumulant functionals associated to (A, ϕ, ϕ ′ ), obtained essentially by "taking a formal derivative with respect to ϕ" in the formulas describing the free cumulants of ϕ. In terms of cumulants, the infinitesimal free independence of a family of unital subalgebras A 1 , .…”
Section: Description Of Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…, A k . One has, as found in [11], a natural way of defining a family (κ ′ n : A n → C) ∞ n=1 of infinitesimal free cumulant functionals associated to (A, ϕ, ϕ ′ ), obtained essentially by "taking a formal derivative with respect to ϕ" in the formulas describing the free cumulants of ϕ. In terms of cumulants, the infinitesimal free independence of a family of unital subalgebras A 1 , .…”
Section: Description Of Frameworkmentioning
confidence: 99%
“…Another way of thinking about Equations (3.6) and (3.7) goes by treating the double sums on their right-hand sides as single sums over certain sets of non-crossing partitions "of type B" (cf. [11], also [10]; a brief review of this point of view is shown in Section 5.1 below).…”
Section: Review Of Infinitesimal Free Cumulants Associated To a Triplementioning
confidence: 99%
See 2 more Smart Citations
“…Our construction of type B Fock space uses the geometry and length function of Coxeter groups based on simple roots, but the main idea of the paper [9] is to use all roots and another length function. Recently, connections between type B and infinitesimal free probability were put into evidence in [7,32,28,27].…”
Section: Introductionmentioning
confidence: 99%